Unethical Marketing and its Consequences on Customer Loyalty - Maksuti , Eduina (European Journal of Economics and Business Studies, 2023)
Unethical marketing is a practice that includes deception, manipulating or misusing customers for the benefit of a business. It can be presented in various forms and methods, such as amplifying or changing the truth, covering important information, targeting special/vulnerable groups, using improbable or transformed images and adverts, or implementing strong sales strategies. This research discusses the concept of unethical marketing and its extensive consequences on customer loyalty. The adaptation of unethical marketing strategies can affect customer satisfaction due to fact that the customers who are involved in may suffer a mix of negative feelings towards the company and the brand itself. These negative emotions can agitate the customers, decrease their loyalty and disconnect them from the company. It can also lead to counter advertisement because the customers may go public or speak on social networks about the company and brand thus damaging its reputation. The use of unethical marketing is considered a short-sighted strategy used by companies with the intention of maximising the number of customers, fast selling the products and become part of the so-called big business. However, this strategy practically has shown to have e very short life and become a boomerang for the company. For these reasons companies should implement ethical marketing strategies that are based on transparency and trust so that they can increase customer loyalty.
Keywords: unethical marketing, customer loyalty, ethical marketing.